A SiO x Aerogel materials, preparation methods and applications

By preparing SiOX gas gel material, the problem of large changes in the volume of lithium -ion battery silicon negative materials in the lithium/off -lithium loss of lithium -ion battery, and realized the negative electrode material of lithium -ion battery with high ratio and structural integrity, which improved the battery Cycle stability and electrochemical storage performance.

CN117185304BActive Publication Date: 2025-01-28NANJING TECH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311149214.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-01-28
Estimated Expiration
2043-09-07

AI Technical Summary

Technical Problem

The volume of the silicon negative electrode material of existing lithium-ion batteries changes greatly during the lithiation/delithation process, resulting in material expansion, loss of electrical contact, repeated formation and rupture of solid phase electrolyte layer, which in turn leads to electrolyte consumption, increase of electrode impedance and capacity attenuation. .

Method used

Use SIOX gas gel material as a lithium -ion battery negative electrode material. After mixing with the surface activated agent and silicon source, after the oxidation of nano -silicon powder plasma is oxidized, it is prepared by ultrasonic dispersing, gel treatment, solvent replacement and heat treatment. SIOX gas gel material with high ratio surface area and pore rate.

Benefits of technology

The high ratio and structural integrity of the lithium -ion battery are realized, the adverse effects of the expansion of the material on the electrode are reduced, and the cycle stability of the battery and the electrochemical storage performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185304B_ABST
    Figure CN117185304B_ABST
Patent Text Reader

Abstract

The invention discloses a SiO x Aerogel material, preparation method and application, silicon powder and anhydrous ethanol are uniformly mixed, a surfactant is introduced to make it uniformly dispersed, and a silane coupling agent which can be used as a coagulant and a silicon source is introduced to obtain Si / SiO2 composite aerogel through sol-gel, aging, solvent replacement, and drying treatment, and then a high-temperature thermal reduction reaction is carried out under the protection of an inert or reducing atmosphere gas to finally prepare SiO2 for lithium-ion battery negative electrode materials. x (x~[1~2]) aerogel. The process adopted by the present invention has the advantages of simple materials and simple process, and the process operation is simple and easy to achieve large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of new materials and relates to a SiO x Aerogel materials, preparation methods and applications. Background Art

[0002] Silicon anode materials have an extremely high theoretical specific capacity (4200mAh / g), which is more than ten times the capacity of graphite. They are considered to be the most promising candidate for lithium-ion batteries (LIBs) anode materials. However, the volume of silicon will change greatly (>400%) during the lithiation / delithiation process, causing the particles to pulverize, lose electrical contact with the conductive agent or current collector, and even fall off the current collector. It will also cause the solid electrolyte layer (SEI) film to form and rupture repeatedly, resulting in continuous consumption of electrolyte, increased electrode impedance, and rapid capacity decay. Silicon dioxide (SiO) as a lithium-ion battery anode material has a high theoretical specific capacity (~2043mAh∙g−1) and a suitable delithiation potential (<0.5 V). In addition, it has abundant raw material reserves, low preparation cost, and is environmentally friendly. It is considered to be a very promising candidate material for the next generation of high energy density lithium-ion battery anodes. Aerogel is a porous material with a three-dimensional network structure, which has the characteristics of low density, high specific surface area, and high porosity. Summary of the invention

[0003] Purpose of the invention: The technical problem to be solved by the present invention is to provide a SiO2 anode material for lithium-ion batteries, which is anode materials with low energy density and expansion problems. x Aerogel material.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A SiO x The method for preparing aerogel material comprises the following steps:

[0006] (1) Nano-silicon powder, surfactant and anhydrous ethanol are mixed and sealed, and then ultrasonically dispersed to obtain a homogeneous silicon suspension;

[0007] (2) uniformly mixing the silicon source, water, acid and the silicon suspension obtained in step (1), then adding alkali and stirring thoroughly to obtain a homogeneous Si / SiO2 binary sol system;

[0008] (3) subjecting the Si / SiO2 binary sol system obtained in step (2) to gelation treatment to obtain Si / SiO2 wet gel;

[0009] (4) adding an aging solution to the Si / SiO2 wet gel obtained in step (3) to perform solvent replacement;

[0010] (5) drying the Si / SiO2 wet gel after solvent replacement in step (4) to obtain Si / SiO2 aerogel;

[0011] (6) The Si / SiO2 aerogel obtained in step (5) is subjected to heat treatment under a protective atmosphere to obtain a

[0012] Furthermore, in step (1), the nano silicon powder has a particle size of 50-100 nm, and the nano silicon powder is subjected to plasma oxidation treatment in a vacuum atmosphere for 5-10 minutes using a plasma oxidizer to graft hydroxyl groups on the silicon surface;

[0013] The surfactant is any one of Triton X-100, cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), polyethylene oxide-block polypropylene oxide-block-polyethylene oxide triblock copolymer (F127), sodium stearate, sodium dodecyl sulfate, and calcium dodecylbenzene sulfonate, or a mixture of two or more thereof; the ultrasonic dispersion is carried out at a constant temperature of 25°C for 30 to 60 minutes.

[0014] Furthermore, in step (2), the silicon source is any one of tetraethyl orthosilicate (TEOS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), triaminopropyltriethoxysilane (APTES), and dimethyldimethoxysilane (DMDMS), or a mixture of two or more thereof, which can be used as both a coagulant and a silicon source; the acid is any one of hydrochloric acid, acetic acid, sulfuric acid, and nitric acid, or a mixture of two or more thereof; and the alkali is any one of ammonia water, sodium hydroxide, and potassium hydroxide, or a mixture of two or more thereof.

[0015] Furthermore, in step (2), in the homogeneous Si / SiO2 binary sol system, the nano-silicon powder, silicon source, anhydrous ethanol, water, surfactant, acid, and alkali are in the order of (1-3): 1: (10-30): 3: (1×10 -5 ~5×10 -5 ):(1×10 -6 ~5×10 -6 ):(5×10 -5 ~1×10 -4 ) in a molar ratio.

[0016] Furthermore, in step (3), the Si / SiO2 binary sol system is poured into a mold and allowed to stand at a temperature of 20-60°C for 2-48 hours to perform gelation treatment.

[0017] Furthermore, in step (4), the aging liquid is any one of ethanol, methanol, acetone, ether, n-pentanol or isopropanol, or a mixture of two or more thereof, and the solvent replacement can be carried out in an oven at a temperature of 35 to 60° C., the number of replacements is 5 to 10 times, and the time for each replacement is 6 to 24 hours.

[0018] Furthermore, in step (5), the drying is carried out by any one of carbon dioxide supercritical drying method, ethanol supercritical drying method and vacuum drying method.

[0019] Furthermore, the heat treatment conditions are: heating to 800~1200°C at a heating rate of 2~10°C / min, and heat treatment for 4~10 hours; the protective atmosphere is an inert or reducing atmosphere, including but not limited to argon, nitrogen, helium or argon-hydrogen mixture.

[0020] Furthermore, the present invention also claims to protect the SiO prepared by the above preparation method. x Aerogel material, the obtained SiO x In aerogel materials, 1≤x≤2.

[0021] Furthermore, the present invention also claims the above-mentioned SiO x Application of aerogel materials in the preparation of negative electrode materials for lithium-ion batteries. Beneficial Effects

[0022] (1) The preparation process of the present invention is simple. The Si / SiO2 aerogel is generated by the acid-base two-step method, and the silicon powder with surface grafted hydroxyl groups is introduced at the same time, and then through the subsequent drying and reduction process, a high specific surface area SiO2 aerogel is finally generated. x (x~[1,2]) phase aerogel.

[0023] (2) The method of the present invention realizes in-situ generation of SiO x The present invention obtains Si / SiO2 aerogel under an inert or reducing atmosphere, so the three-dimensional structure is more complete. At the same time, due to the existence of the aerogel three-dimensional skeleton of the aerogel itself, the prepared material has a higher porosity and a larger specific surface area, and the specific capacity of the prepared lithium-ion battery is higher.

[0024] (3) SiO prepared by the present invention x The aerogel material is in a complete block, which further improves the structural integrity and antioxidant properties of the silica material, which has positive significance for the application of silica aerogel in the field of electrochemical storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0026] Figure 1 The SiO prepared in Example 1 x Physical picture of aerogel material samples.

[0027] Figure 2 The SiO prepared in Example 1 x XRD pattern of aerogel material.

[0028] Figure 3 The SiO prepared in Example 1 x Cyclic charge and discharge specific capacity-voltage curve of lithium-ion battery prepared with aerogel material. DETAILED DESCRIPTION

[0029] The present invention can be better understood with reference to the following examples. Example 1

[0030] The nano-silicon powder was subjected to plasma oxidation treatment in a vacuum atmosphere for 5 min using a plasma oxidation apparatus to graft hydroxyl groups on the silicon surface. The plasma-oxidized nano-silicon powder (80 nm), anhydrous ethanol, and Triton X-100 were mixed in a molar ratio of 2:16.5:1.5×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 minutes to obtain a homogeneous silicon suspension; then tetraethyl orthosilicate, deionized water, and hydrochloric acid (1M) were mixed with nano-silicon powder at a molar ratio of 1:3:3×10 -6 :2 After uniform mixing, stir at 25℃ for 90min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 15:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ethanol aging liquid after standing for 12h, and perform solvent replacement in an oven at 50℃ for 3 times, each time for 24h. Then the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1200℃ under the protection of argon-hydrogen mixed gas atmosphere, with a heating rate of 5℃ / min and insulation for 6h to obtain blocky SiO x Aerogel materials. Figure 1 As shown, the SiO x The actual sample of aerogel material is brown-gray. After characterization, it was found that the block SiO x The density of aerogel material is 0.15g / cm 3 , with a specific surface area of ​​524m 2 / g, and the pore size is mainly distributed around 20nm. Figure 2 The SiO prepared in Example 1 xThe XRD diagram of aerogel material shows that the main components are Si, SiO and SiO2. x Aerogel (80wt%) was mixed with polyvinylidene fluoride (PVDF, 10wt%) and acetylene black (10wt%) in N-methyl-2-pyrrolidone (NMP) and stirred until uniform slurry was formed. The slurry was coated on the surface of the copper foil current collector and then dried in a vacuum oven at 80°C for 12 hours to remove N-methyl-2-pyrrolidone. The copper foil was pressed and punched into an electrode sheet with a diameter of 13 mm. The electrolyte used LiPF6 (1.0 M) in ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (EC:DMC:EMC=1:1:1 Vol%). Polypropylene foil was used as the battery separator. The battery was assembled in an argon-filled glove box. Combined Figure 3 As shown, the lithium-ion battery made of this material has a first discharge specific capacity of up to 813 mAh / g, a first charge specific capacity of up to 574 mAh / g, and a first coulombic efficiency of 70.59%. Example 2

[0031] The nano-silicon powder was subjected to plasma oxidation treatment in a vacuum atmosphere for 10 min to graft hydroxyl groups on the silicon surface. The plasma-oxidized nano-silicon powder (50 nm), anhydrous ethanol, and hexadecyltrimethylammonium bromide (CTAB) were mixed in a molar ratio of 2:10:1×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 min to obtain a homogeneous silicon suspension; then methyltrimethoxysilane (MTMS), deionized water, and hydrochloric acid (1 M) were mixed in a molar ratio of 1:3:1×10 -6 :1 and then stirred at 30°C for 100 minutes to obtain a homogeneous Si / SiO2 binary sol system; then ammonia water was added to the above binary sol system at a molar ratio of 20:1 to hydrochloric acid, and stirring was continued for 10 minutes; then poured into a mold to react to gel, and after standing for 24 hours, methanol aging liquid was added, and the solvent was replaced in an oven at 35°C for 6 times, each time for 12 hours. Then the wet gel was subjected to ethanol supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel was heat treated at 800°C under the protection of an argon-hydrogen mixed gas atmosphere, with a heating rate of 2°C / min and a heat preservation of 4 hours to obtain a block of SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.13g / cm 3 , with a specific surface area of ​​632m 2 / g, and the pore size is mainly distributed around 10nm. The lithium-ion battery made of this material has a first discharge capacity of 1200mAh / g, a first charge capacity of 650mAh / g, and a first coulombic efficiency of 54%. Example 3

[0032] The nano-silicon powder was plasma oxidized for 7 minutes in a vacuum atmosphere using a plasma oxidizer to graft hydroxyl groups on the silicon surface. The plasma oxidized nano-silicon powder (60 nm), anhydrous ethanol, and hexadecyltrimethylammonium chloride (CTAC) were mixed in a molar ratio of 2:15:2×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 min to obtain a homogeneous silicon suspension; then methyltriethoxysilane (MTES), deionized water, and sulfuric acid (1 M) were mixed with nano-silicon powder at a molar ratio of 1:3:3×10 -6 :2 After uniform mixing, stir at 35°C for 90 minutes to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 50:1 to sulfuric acid, and continue stirring for 5 minutes; then pour it into a mold to react to gel, add acetone aging solution after standing for 2 hours, and perform solvent replacement in an oven at 40°C for 12 times, each time for 6 hours. Then the wet gel is dried at normal pressure to obtain a Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1000°C under argon atmosphere protection, with a heating rate of 5°C / min and insulation for 8 hours to obtain a block of SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.23g / cm 3 , with a specific surface area of ​​241m 2 / g, and the pore size is mainly distributed around 8nm. The lithium-ion battery made of this material has a first discharge capacity of up to 950mAh / g, a first charge capacity of up to 550mAh / g, and a first coulombic efficiency of 57.89%. Example 4

[0033] The nano-silicon powder was plasma oxidized for 5 min in a vacuum atmosphere using a plasma oxidizer to graft hydroxyl groups on the silicon surface. The plasma oxidized nano-silicon powder (100 nm), anhydrous ethanol, and polyethylene oxide-block polypropylene oxide-block-polyethylene oxide triblock copolymer (F127) were mixed in a molar ratio of 2:20:5×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 60 min to obtain a homogeneous silicon suspension; then triaminopropyltriethoxysilane (APTES), deionized water, and acetic acid (1 M) were mixed with nano-silicon powder at a molar ratio of 1:3:5×10 -6:3 After uniform mixing, stir at 40℃ for 120min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 50:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ether aging liquid after standing for 2h, and perform solvent replacement in an oven at 35℃ for 5 times, each time for 12h. Then, the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1200℃ under nitrogen atmosphere protection, with a heating rate of 5℃ / min and kept warm for 10h to obtain blocky SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.18g / cm 3 , with a specific surface area of ​​451m 2 / g, and the pore size is mainly distributed around 16nm. The lithium-ion battery made of this material has a first discharge capacity of 825mAh / g, a first charge capacity of 537mAh / g, and a first coulombic efficiency of 65%. Example 5

[0034] The nano-silicon powder was subjected to plasma oxidation treatment in a vacuum atmosphere for 5 min using a plasma oxidation apparatus to graft hydroxyl groups onto the silicon surface. The plasma-oxidized nano-silicon powder (90 nm), anhydrous ethanol, and sodium stearate were mixed in a molar ratio of 2:16.5:3×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 min to obtain a homogeneous silicon suspension; then dimethyldimethoxysilane (DMDMS), deionized water, and nitric acid (1 M) were mixed in a molar ratio of 1:3:4×10 -6 :2 After uniform mixing, stir at 45℃ for 90min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 15:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ethanol aging liquid after standing for 12h, and perform solvent replacement in an oven at 50℃ for 3 times, each time for 24h. Then the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1200℃ under the protection of argon-hydrogen mixed gas atmosphere, with a heating rate of 5℃ / min and heat preservation for 6h, thereby obtaining blocky SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.17g / cm 3 , with a specific surface area of ​​632m 2 / g, and the pore size is mainly distributed around 18nm. The lithium-ion battery made of this material has a first discharge capacity of 920mAh / g, a first charge capacity of 530mAh / g, and a first coulombic efficiency of 57.6%. Example 6

[0035] The nano-silicon powder was subjected to plasma oxidation treatment in a vacuum atmosphere for 5 min to graft hydroxyl groups on the silicon surface. The plasma-oxidized nano-silicon powder (60 nm), anhydrous ethanol, and sodium dodecyl sulfate were mixed in a molar ratio of 2:16.5:1.5×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 minutes to obtain a homogeneous silicon suspension; then tetraethyl orthosilicate, deionized water, and hydrochloric acid (1M) were mixed with nano-silicon powder at a molar ratio of 1:3:3×10 -6 :2 After uniform mixing, stir at 50℃ for 90min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 15:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ethanol aging liquid after standing for 12h, and perform solvent replacement in an oven at 25℃ for 3 times, each time for 24h. Then the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1200℃ under the protection of argon-hydrogen mixed gas atmosphere, with a heating rate of 5℃ / min and heat preservation for 6h, thereby obtaining a block of SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.19g / cm 3 , with a specific surface area of ​​451m 2 / g, and the pore size is mainly distributed around 20nm. The lithium-ion battery made of this material has a first discharge capacity of 980mAh / g, a first charge capacity of 420mAh / g, and a first coulombic efficiency of 42.8%. Example 7

[0036] Nano-silicon powder was plasma oxidized in a vacuum atmosphere for 5 min (70 nm) using a plasma oxidizer, anhydrous ethanol, and calcium dodecylbenzenesulfonate in a molar ratio of 2:16.5:1.5×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 minutes to obtain a homogeneous silicon suspension; then tetraethyl orthosilicate, deionized water, and hydrochloric acid (1M) were mixed with nano-silicon powder at a molar ratio of 1:3:3×10 -6:2 After uniform mixing, stir at 25℃ for 90min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 15:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ethanol aging liquid after standing for 12h, and perform solvent replacement in an oven at 50℃ for 3 times, each time for 24h. Then the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1200℃ under the protection of argon-hydrogen mixed gas atmosphere, with a heating rate of 5℃ / min and insulation for 6h to obtain blocky SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.12g / cm 3 , with a specific surface area of ​​358m 2 / g, and the pore size is mainly distributed around 10nm. The lithium-ion battery made of this material has a first discharge capacity of 970mAh / g, a first charge capacity of 510mAh / g, and a first coulombic efficiency of 52.6%. Example 8

[0037] Nano-silicon powder was plasma oxidized in a vacuum atmosphere for 5 min (80 nm) using a plasma oxidizer, anhydrous ethanol, and Triton X-100 in a molar ratio of 2:25:1.5×10 -5 After uniform mixing and sealing, ultrasonic dispersion was performed at a constant temperature of 25°C for 30 minutes to obtain a homogeneous silicon suspension; then tetraethyl orthosilicate, deionized water, and hydrochloric acid (1M) were mixed with nano-silicon powder at a molar ratio of 1:3:3×10 -6 :2 After uniform mixing, stir at 30℃ for 120min to obtain a homogeneous Si / SiO2 binary sol system; then add ammonia water to the above binary sol system at a molar ratio of 15:1 with hydrochloric acid, and continue stirring for 5min; then pour it into a mold to react to gel, add ethanol aging liquid after standing for 12h, and perform solvent replacement in an oven at 50℃ for 3 times, each time for 24h. Then the wet gel is subjected to CO2 supercritical drying to obtain Si / SiO2 composite aerogel. The composite aerogel is heat treated at 1000℃ under the protection of argon-hydrogen mixed gas atmosphere, with a heating rate of 10℃ / min and insulation for 10h to obtain blocky SiO x Aerogel material. After characterization, it was found that the bulk SiO x The density of aerogel material is 0.18g / cm 3 , with a specific surface area of ​​305m 2 / g, and the pore size is mainly distributed around 15nm. The lithium-ion battery made of this material has a first discharge capacity of 980mAh / g, a first charge capacity of 491mAh / g, and a first coulombic efficiency of 50.1%.

[0038] The present invention provides a SiO x There are many methods and approaches to realize the aerogel material, preparation method and application, and the above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A SiO x A method for preparing an aerogel material, characterized in that: The steps include: (1) Nano-silicon powder, surfactant and anhydrous ethanol are mixed and sealed, and then ultrasonically dispersed to obtain a homogeneous silicon suspension; (2) uniformly mixing the silicon source, water, acid and the silicon suspension obtained in step (1), then adding alkali and stirring thoroughly to obtain a homogeneous Si / SiO2 binary sol system; (3) subjecting the Si / SiO2 binary sol system obtained in step (2) to gelation treatment to obtain Si / SiO2 wet gel; (4) adding an aging solution to the Si / SiO2 wet gel obtained in step (3) to perform solvent replacement; (5) drying the Si / SiO2 wet gel after solvent replacement in step (4) to obtain Si / SiO2 aerogel; (6) The Si / SiO2 aerogel obtained in step (5) is subjected to heat treatment under a protective atmosphere to obtain a 2. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (1), the nano silicon powder has a particle size of 50-100 nm, and the nano silicon powder is subjected to plasma oxidation treatment in a vacuum atmosphere for 5-10 minutes using a plasma oxidation apparatus to graft hydroxyl groups on the silicon surface; The surfactant is any one of Triton X-100, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, polyethylene oxide-block polypropylene oxide-block-polyethylene oxide triblock copolymer, sodium stearate, sodium dodecyl sulfate, and calcium dodecylbenzenesulfonate, or a mixture of two or more thereof; the ultrasonic dispersion is carried out at a constant temperature of 25° C. for 30 to 60 minutes.

3. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (2), the silicon source is any one of tetraethyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, triaminopropyltriethoxysilane, dimethyldimethoxysilane, or a mixture of two or more thereof; the acid is any one of hydrochloric acid, acetic acid, sulfuric acid, or nitric acid, or a mixture of two or more thereof; and the base is any one of ammonia water, sodium hydroxide, or potassium hydroxide, or a mixture of two or more thereof.

4. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (2), in the homogeneous Si / SiO2 binary sol system, nano silicon powder, silicon source, anhydrous ethanol, water, surfactant, acid, and alkali are in the order of (1-3): 1: (10-30): 3: (1×10 -5 ~5×10 -5 ):(1×10 -6 ~5×10 -6 ):(5×10 -5 ~1×10 -4 ) in a molar ratio.

5. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (3), the Si / SiO2 binary sol system is poured into a mold and allowed to stand at a temperature of 20-60° C. for 2-48 hours to perform gelation treatment.

6. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (4), the aging liquid is any one of ethanol, methanol, acetone, ether, n-pentanol or isopropanol, or a mixture of two or more thereof. The temperature of solvent replacement is 35 to 60° C., the number of replacements is 5 to 10 times, and the time for each replacement is 6 to 24 hours.

7. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (5), the drying is carried out by any one of carbon dioxide supercritical drying method, ethanol supercritical drying method and vacuum drying method.

8. SiO according to claim 1 x A method for preparing an aerogel material, characterized in that: In step (6), the heat treatment conditions are: heating to 800-1200°C at a heating rate of 2-10°C / min, and heat treatment for 4-10 hours; the protective atmosphere is argon, nitrogen, helium or a mixture of argon and hydrogen.

9. SiO prepared by the preparation method according to any one of claims 1 to 8 x Aerogel material, characterized in that The obtained SiO x In aerogel materials, 1≤x≤2.

10. SiO according to claim 9 x Application of aerogel materials in the preparation of negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN114023948A

  • Method for preparing silicon oxide aerogel by using alkaline silica sol

    CN114538454A